Improvement of autism spectrum disorder symptoms in three children by using gastrin‐releasing peptide - Michele Michelin Becker; Cleonice Bosa; Vera Lorentz Oliveira‐Freitas; José Roberto Goldim; Lygia Ohlweiler; Rafael Roesler; Gilberto Schwartsmann; Rudimar dos Santos Riesgo (Brazilian Society of Pediatrics, 2016)
Objective: To evaluate the safety, tolerability and potential therapeutic effects of gastrin‐releasing peptide in three children with autistic spectrum disorder. Methods: Case series study with the intravenous administration of gastrin‐releasing peptide in the dose of 160 pmol/kg for four consecutive days. To evaluate the results, parental impressions the Childhood Autism Rating Scale (CARS) and the Clinical Global Impression (CGI) Scale. Each child underwent a new peptide cycle after two weeks. The children were followed for four weeks after the end of the infusions. Results: The gastrin‐releasing peptide was well tolerated and no child had adverse effects. Two children had improved social interaction, with a slight improvement in joint attention and the interaction initiatives. Two showed reduction of stereotypes and improvement in verbal language. One child lost his compulsion to bathe, an effect that lasted two weeks after each infusion cycle. Average reduction in CARS score was 2.8 points. CGI was "minimally better" in two children and "much better" in one. Conclusions: This study suggests that the gastrin‐releasing peptide is safe and may be effective in improving key symptoms of autism spectrum disorder, but its results should be interpreted with caution. Controlled clinical trials-randomized, double‐blinded, and with more children-are needed to better evaluate the possible therapeutic effects of gastrin‐releasing peptide in autism.